2002
DOI: 10.1073/pnas.212448699
|View full text |Cite
|
Sign up to set email alerts
|

The tomato fer gene encoding a bHLH protein controls iron-uptake responses in roots

Abstract: Iron deficiency is among the most common nutritional disorders in plants. To cope with low iron supply, plants with the exception of the Gramineae increase the solubility and uptake of iron by inducing physiological and developmental alterations including iron reduction, soil acidification, Fe(II) transport and root-hair proliferation (strategy I). The chlorotic tomato fer mutant fails to activate the strategy I. It was shown previously that the fer gene is required in the root. Here, we show that fer plants e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
334
2
3

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 360 publications
(354 citation statements)
references
References 30 publications
12
334
2
3
Order By: Relevance
“…Iron (Fe)-deficiency induced transcription factor (FIT) is a basic helix-loop-helix (bHLH) family transcription factor induced by iron deficiency at the transcriptional level. The role of FIT is in iron homeostasis, regulating the expression of IRT1 and FRO2 in species of Arabidopsis and tomato (Ling et al, 2002;Colangelo and Guerinot, 2004;Jakoby et al, 2004;Yuan et al, 2005). Yuan et al (2008) and Wang et al (2012) proposed that FIT forms a complex with other iron-deficiencyinduced bHLH transcription factors such as bHLH38, bHLH39, bHLH100 and bHLH101.…”
Section: Introductionmentioning
confidence: 99%
“…Iron (Fe)-deficiency induced transcription factor (FIT) is a basic helix-loop-helix (bHLH) family transcription factor induced by iron deficiency at the transcriptional level. The role of FIT is in iron homeostasis, regulating the expression of IRT1 and FRO2 in species of Arabidopsis and tomato (Ling et al, 2002;Colangelo and Guerinot, 2004;Jakoby et al, 2004;Yuan et al, 2005). Yuan et al (2008) and Wang et al (2012) proposed that FIT forms a complex with other iron-deficiencyinduced bHLH transcription factors such as bHLH38, bHLH39, bHLH100 and bHLH101.…”
Section: Introductionmentioning
confidence: 99%
“…FER and FIT share higher sequence similarity with each other rather than with any other known bHLH protein from the two species. FER is required for induction of iron reductase and iron transporter genes in tomato (Ling et al 2002;Bereczky et al 2003;Bauer et al 2004;Li et al 2004). FIT was found essential for the induction of FRO2 upon iron deWciency in Arabidopsis (Colangelo and Guerinot 2004;Jakoby et al 2004) as well as for induction of IRT1 (Jakoby et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…One allele has a T-DNA insertion in an exon (Wt-3 = fru-G108), the other allele contains a premature EMS-induced stop codon in an exon (Jakoby et al 2004). Loss of function of FER and FIT resulted in lethal leaf chlorosis due to insuYcient iron uptake in tomato and in Arabidopsis (Ling et al 2002;Colangelo and Guerinot 2004;Jakoby et al 2004). Expression of FER and FIT was induced by low iron supply compared to suYcient and/or generous iron supply suggesting that iron mobilization is controlled by a cascade of transcription factors with FER/FIT genes being part of it.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that long distance signaling from the shoot to the roots is key to regulating iron uptake in the roots [5]. However, there is still a significant gap and virtually no progress has been made in our understanding on how plants sense their iron status and how the signals are transduced across the plant toward the root cells to induce or repress the expression of key genes involved in iron homeostasis such as the genes coding for ferric reductases (FRO) or the iron transporters (IRT1, IRT2).As pointed out by Chen et al in their article of this issue of Cell Research [6], there are only two accounts in the literature describing transcription factors involved in the regulation of iron metabolism in plants [7,8]. Therefore the work reported by Chen et al is of significant importance in the quest to identifying key regulatory genes involved in iron homeostasis.…”
mentioning
confidence: 99%
“…As pointed out by Chen et al in their article of this issue of Cell Research [6], there are only two accounts in the literature describing transcription factors involved in the regulation of iron metabolism in plants [7,8]. Therefore the work reported by Chen et al is of significant importance in the quest to identifying key regulatory genes involved in iron homeostasis.…”
mentioning
confidence: 99%